‘I said it!’ ‘I’m first!’: gender and language-learner identities - Peña, Harold Andrés (Colombian Applied Linguistics Journal, 2008)
While there has been an upsurge of research studying the relationship of gender and second language learning in cross-cultural contexts, far less has been investigated about preschool children’s gender and learner identities in contexts where English is a foreign language. In this paper I describe how gendered discourses are at stake in the classroom and how these discourses are related to the learner identities of a group of Colombian preschoolers. I use a Feminist Poststructuralist Discourse Analysis (FPDA) approach to pin down moments in which the assertion of power is manifested in second language practices like ‘classroom races’ during literacy activities. This assertion of power positions participants differently. Findings suggest the need to understand how children negotiate subject positions discursively in language learning activities. I am suggesting the need to erode discourses of approval that marginalize girls and favour boys.